2005
DOI: 10.1051/rnd:2005019
|View full text |Cite
|
Sign up to set email alerts
|

Particularities of reproduction and oogenesis in teleost fish compared to mammals

Abstract: -Compared to mammals, teleost reproduction presents many original features. Reproductive strategies of species are diversified into numerous adaptations to a large variety of aquatic environments. This diversity may concern sexuality, spawning and parental behaviour, sensitivity to environmental factors, and specific features of gametogenesis such as the duration of vitellogenesis, and egg morphology. Sexuality presents a variety of natural modalities, from gonochorism to hermaphrodism. The absence of definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
1
17

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(128 citation statements)
references
References 135 publications
(122 reference statements)
7
102
1
17
Order By: Relevance
“…According to BAZOLLI & GODINHO (1997), these structures contain neutral glycoproteins that are released into the perivitellinic space in order to block polyspermy after fertilization (MICALE et al 1999). During secondary growth, the oocyte increases its diameter due to the accumulation of yolk (JALABERT 2005). It was observed that the vitellogenic oocytes in L. alexandri increased their diameter in ca.…”
Section: Discussionmentioning
confidence: 99%
“…According to BAZOLLI & GODINHO (1997), these structures contain neutral glycoproteins that are released into the perivitellinic space in order to block polyspermy after fertilization (MICALE et al 1999). During secondary growth, the oocyte increases its diameter due to the accumulation of yolk (JALABERT 2005). It was observed that the vitellogenic oocytes in L. alexandri increased their diameter in ca.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with mammals, fish reproduction modes and strategies exhibit abundant diversities and extreme particularities [49,50]. Owing to the diversities and particularities, much attention has begun to be paid to some important fish with special reproduction modes.…”
Section: Reproduction Trait and Candidate Reproductionrelated Genesmentioning
confidence: 99%
“…Oocytes, and their surrounding follicular cells, representing different stages of follicle development, both produce and respond to different types of signaling molecules during maturation (Jalabert, 2005;Lubzens et al, 2009), and thus would be expected to have different transcription profiles depending on their relative stage of maturation. Consequently, when studying the effects of chemical contaminants or other stressors on ovarian transcript profiles, chemical effects must be interpreted over a background signal which is dependent on the relative number and proportions of different staged follicles present within the ovary.…”
Section: Introductionmentioning
confidence: 99%